2009
DOI: 10.1002/ibd.20839
|View full text |Cite
|
Sign up to set email alerts
|

Fear and fertility in inflammatory bowel disease: A mismatch of perception and reality affects family planning decisions

Abstract: The unusually high response rate indicates the centrality of reproductive issues to IBD patients. "Voluntary" childlessness in this group appears to result from concerns about adverse reproductive outcomes that may not be justified. Patients require accurate counseling addressing fertility and pregnancy outcomes in IBD to assist in their decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
175
2
16

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(200 citation statements)
references
References 30 publications
7
175
2
16
Order By: Relevance
“…How well this message has been communicated to patients, and to what extent the advice is acted upon has however been little studied. Previous research conducted in Australia showed that women with IBD were fearful of the effects of medication upon pregnancy with 30% specifically fearing congenital anomalies 38 and as many as 84% fearing some adverse effect upon the pregnancy 14 . We also have data from Denmark where studies in UC and CD have demonstrated that not only do women with IBD fear the effects of their medications, but this also leads to reduced adherence 20,21 .…”
Section: Interpretation In the Context Of Previous Literaturementioning
confidence: 99%
“…How well this message has been communicated to patients, and to what extent the advice is acted upon has however been little studied. Previous research conducted in Australia showed that women with IBD were fearful of the effects of medication upon pregnancy with 30% specifically fearing congenital anomalies 38 and as many as 84% fearing some adverse effect upon the pregnancy 14 . We also have data from Denmark where studies in UC and CD have demonstrated that not only do women with IBD fear the effects of their medications, but this also leads to reduced adherence 20,21 .…”
Section: Interpretation In the Context Of Previous Literaturementioning
confidence: 99%
“…Women with IBD are more likely to seek information about contraception and reproductive health from their gastroenterologist than from a family care physician, although most of this counseling is initiated by patients [24]. Yet most patients seeing a gastroenterologist have no documented reproductive counseling and 41% of general practitioners report that they never raise the issue of family planning with their IBD patients [12].…”
Section: Discussionmentioning
confidence: 99%
“…Dyspareunia (painful sexual congress) often occurs secondary to pelvic surgery, from IBD-associated inflammation, or psychological stress associated with IBD. Interestingly, the main cause of decreased rates of fertility in CD patients with history of previous surgeries was found to be a conscious and concerted decision against conception [17] . For women with inactive IBD and without history of pelvic surgery, fertility is however comparable to their respective age-matched peers [18] .…”
Section: Fertilitymentioning
confidence: 99%